Theory of edge diffraction in electromagnetics origination and validation of the physical theory of diffraction - Ufimtsev, Pyotr Yakovlevich (SciTech Publishing, 2009)
The following topics are dealt with: electromagnetic wave diffraction; black bodies: Kirchhoff-Kottler theory; edge diffraction; convex perfectly conducting bodies; concave surfaces; radiation measurement; diffraction/nonuniform currents; wedge diffraction; parabolic equation; thin conductors and strips; edge waves radiation; reciprocity theorem; strip diffraction; integral equations; plane wave diffraction; and open-ended parallel plate resonator.